DNA sequence organization of IS10-right of Tn10 and comparison with IS10-left - Halling, S. M. (1982)
Tn10 is 9,300 base pairs long and has inverted repeats of an insertion sequence (IS)-like sequence (IS10) at its ends. IS10-right provides all of the Tn10-encoded functions used for normal Tn10 transposition. IS10-left can also provide these functions but at a much reduced level. We report here the complete nucleotide sequence of IS10-right and a partial sequence of IS10-left. From our analysis of this information, we draw the following conclusions. (i) IS10-right is 1,329 base pairs long. Like most IS elements, it has short (23-base pair) nearly perfect inverted repeats at its termini. We can divide these 23-base pair segments into at least two functionally distinct parts. IS10-right also shares with other elements the presence of a single long coding region that extends the entire length of the element. Genetic evidence suggests that this coding region specifies an essential IS10 transposition function. A second, overlapping, coding region may or may not be important. (ii) The “outside” end of IS10-right contains three suggestively positioned internal symmetries. Two of these (A1 and A2) are nearly identical in sequence. Symmetry A1 overlaps the terminal inverted repeat; symmetry A2 overlaps the promoter shown elsewhere to be responsible for expression of IS10 functions and lies very near a second characterized promoter that directs transcription outward across the end of IS10. Symmetries A1 and A2 may play a role in modulation of Tn10 activity and are likely to function at least in part as protein recognition sites. We propose that the third symmetry (B) acts to prevent fortuitous expression of IS10 functions from external promoters. The transcripts from such promoters can assume a stable secondary structure in which the AUG start codon of the long coding region is sequestered in a region of double-stranded mRNA formed by pairing between the two halves of symmetry B. (iii) IS10-left differs from IS10-right at many nucleotide positions in both the presumptive regulatory region and the long coding region. The available evidence suggests that Tn10 may be older than other analyzed drug-resistance transposons and thus have had more time to accumulate mutational changes.